Studies toward the Synthesis of Iejimalides A–D: Preparation of the C3–11 and C12–C24 Fragments - Sabitha, Gowravaram; Gurumurthy, Ch.; Yadav, Jhillu Singh (Synthesis, 2014)
The convergent synthesis of the C3–C11 and C12–C24 fragments of the iejimalides A–D is described. The C3–C11 fragment is obtained by a cross-metathesis reaction, while the C12–C24 fragment is derived from a Still–Gennari modified Horner–Wadsworth–Emmons olefination.
Keywords: iejimalides; macrolides; cross-metathesis; Horner–Wadsworth–Emmons; fragment synthesis